Respuesta :

━━━━━━━☆☆━━━━━━━

▹ Answer

(4, 2)

▹ Step-by-Step Explanation

2x - y = 6

2x - 2y = 4

2x = 6 + y

2x - 2y = 4

6 + y - 2y = 4

y = 2

2x - 2 * 2 = 4

x = 4

(x, y) = (4, 2)

Hope this helps!

- CloutAnswers ❁

Brainliest is greatly appreciated!

━━━━━━━☆☆━━━━━━━

Answer:

x = 4 and y = 2

Step-by-step explanation:

Using elimination method

2x - y = 6........ 1

2x - 2y = 4 ......... 2

Subtract equation 2 from 1

That's

2x - 2x - y + 2y = 6 - 4

y = 2

Substitute y = 2 into any of the equations

Using equation 1

2x - 2 = 6

2x = 6+2

2x = 8

Divide both sides by 2

x = 4

Therefore x = 4 , y = 2

Hope this helps you